Advancing Performance and Unfolding Mechanism of Lithium and Sodium Storage in SnO2 via Precision Synthesis of Monodisperse PEG‐Ligated Nanoparticles (Adv. Energy Mater. 26/2022). Issue 26 (14th July 2022) - Zhao, Shiqiang; He, Yanjie; Wang, Zewei; Bo, Xiaoxu; Hao, Shumeng; Yuan, Yifei; Jin, Huile; Wang, Shun; Lin, Zhiqun
Abstract : Nanoreactors In article number 2201015, Shun Wang, Zhiqun Lin and co‐workers report the precision crafting of monodisperse PEG‐ligated SnO2 nanoparticles using star‐like PAA‐ b ‐PEG diblock copolymers as nanoreactors which are homogenously anchored on graphene oxide. The surface polymer ligation, precise size control and uniform graphene encapsulation lead to remarkable performance advancement and insights into the mechanism of lithium and sodium storage in SnO2 .